A synthesis on classical Brouwer theory - Schuback, Nelson Orsalino Neto (2021)
In this work we present the fundamentals of Classical Brouwer Theory. We start with the works of L. E. J. Brouwer on translation arcs and the Brouwer translation theo- rem. Next, we explore the notion of maximal free brick decompositions developed by A. Sauzet. Finally, we conclude by presenting a proof of the foliated version of the Brouwer translation theorem, due to P. Le Calvez.